Orexins as Novel Therapeutic Targets in Inflammatory and Neurodegenerative Diseases - Couvineau, Alain; Voisin, Thierry; Nicole, Pascal; Gratio, Valérie; Abad, Catalina; Tan, Yossan-Var (Frontiers in Endocrinology, 2019)
Orexins (orexin-A (OXA) and orexin-B (OXB)) are two isoforms of neuropeptides produced by the hypothalamus. The main biological actions of orexins, focused on the central nervous system, are to control the sleep/wake process, appetite and feeding, energy homeostasis, drug addiction and cognitive processes. These effects are mediated by two G protein-coupled receptor (GPCR) subtypes named OX1R and OX2R. In accordance with the synergic and dynamic relationship between the nervous and immune systems, orexins also have neuroprotective and immuno-regulatory (i.e. anti-inflammatory) properties. The present review gathers recent data demonstrating that orexins may have a therapeutic potential in several pathologies with an immune component including multiple sclerosis, Alzheimer’s disease, narcolepsy, obesity, intestinal bowel diseases, septic shock and cancers.